PERINATAL CARE IN A NORTHEASTERN BRAZILIAN STATE: STRUCTURE, WORK PROCESSES, AND EVALUATION OF THE COMPONENTS OF ESSENTIAL NEWBORN CARE - Felipa Daiana Bezerra; Maria Alexsandra da Silva Menezes; Rosemar Barbosa Mendes; José Marcos de Jesus Santos; Débora Cristina Fontes Leite; Samir Buainain Kassar; Ricardo Queiroz Gurgel (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To describe the structure and the processes of care for pregnant women/newborn infants, including the Essential Newborn Care (ENC), in maternity hospitals in Sergipe State, Brazil. Methods: A cross-sectional study carried out between June 2015 and April 2016 in all maternity hospitals of Sergipe with more than 500 deliveries/year (n=11). A questionnaire on the existing structure and work processes was administered to the managers. Subsequently, a representative number of postpartum women from these hospitals were interviewed (n=768). Their medical records, as well as newborn infants' records, were also analyzed. Results: Sergipe has 78 beds of Neonatal Intensive Care Unit (NICU) and 90 beds of Intermediate Care Unit (IMCU) to meet spontaneous and programmed demand. Only six maternity hospitals (54.5%) performed the risk classification, and four (36.3%) had protocols for high-risk parturient care. Regarding the ENC components, only 41% (n=315) of the women had early skin-to-skin contact with their babies, 33.1% (n=254) breastfed in the first hour of life, and 18% (n=138) had a companion always during birth. Conclusions: The distribution of NICU beds between capital city and other cities of the State is adequate, considering Brazilian guidelines. However, there was a low adherence to the protocols for hypertensive and hemorrhagic emergencies, and a low coverage of humanization policies, pregnancy risk classification and ENC practices, especially breastfeeding in the first hour of life, and companion always during birth.